Application of commercial probiotics in catfish farming - Muh. Sulaiman Dadiono; Rudy Wijaya (Academic Letters, 2025)
Feeding enriched with commercial probiotics is one solution to overcome the challenges in intensive catfish farming, especially related to the high cost of feed. Adding probiotics to feed can help reduce production costs while speeding up harvest time. Commercial probiotics containing bacteria such as *Lactobacillus*, *Acetobacter*, and *yeast* have been proven to be very effective in supporting catfish growth. Based on the advantages that have been revealed in various studies, the use of commercial probiotics is feasible to be applied and further developed in intensive catfish farming.